Civil defense, leadership and heuristics for the education of headquarters for emergency situations - Bereš, Paun J.; Bereš, Kristian P.; Cvetković, Sreten S. (Vojnotehnički glasnik / Military Technical Courier, 2015)
This paper presents solving heuristically conceived problems in the Civil Defence by making adequate decisions in an emergency and the state of emergency with a special emphasis on the application of the heuristic model of training emergency teams-headquarters and on the role of a leader as a factor of good leadership. It is intended for command and teaching staff of the Civil Defence: local authorities (mayors of districts, cities and municipalities - commanders) and the system of protection and rescue (the Sector for Emergency Situations).The heuristic approach to problem solving should enable command staff-leaders from the local to the national level to make adequate decisions in emergency situations after the proclamation of emergency and the state of emergency in a territory part or the whole territory of the Republic of Serbia - functioning of the civil defense and the third mission of the Army of Serbia, as well as to point out the necessity of coordination between the local and national level.
Keywords: leadership; Heuristics; civil defence